Doubling Down on Wicked Problems: Ocean ArtScience Collaborations for a Sustainable Future - Jung, Julia; Gupa, Dennis; Hash, Colton; Thoms, Jol; Owens, Dwight; Threlfall, John; Juniper, S. Kim (Frontiers in Marine Science, 2022)
The UN Decade of Ocean Science for Sustainable Development recognizes the current ocean sustainability crisis and calls for a transformation of ocean science. Many of the key challenges recognized by the UN Decade are examples of wicked problems: intractable and messy situations with high stakeholder divergence. Addressing wicked ocean sustainability problems requires adaptable, iterative, and participatory approaches that can embrace multiple ways of knowing. It also requires a re-imagining of our relationship with the Ocean from extraction and resulting environmental degradation, towards the building of a sense of connection and stewardship. We propose ArtScience as a means to this end by highlighting how transdisciplinary collaborations can help create sustainable ocean futures. We reflect on a recent ArtScience event emerging from Ocean Networks Canada’s Artist-in-Residence programme. By situating ArtScience in a broader context of inter- and transdisciplinary collaborations, we demonstrate how ArtScience collaborations can help transform ocean science by envisioning previously unimagined possibilities, and establishing and strengthening relationships with diverse stakeholders through long-term mission-driven or place-based inquiry. We conclude with a call to action to acknowledge the potential these collaborations hold for addressing the challenges of the UN Ocean Decade.